Children benefit from morphological relatedness when they learn to spell new words - Pacton, Sebastien; Foulin, Jean-Noel; Casalis, Séverine; Treiman, Rebecca (Frontiers in Psychology, 2013)
Use of morphologically related words often helps in selecting among spellings of sounds in French. For instance, final /wa/ may be spelled oi (e.g., envoi ‘sendoff’), oit (e.g., exploit ‘exploit’), ois (e.g., siamois, ‘siamese’), or oie (e.g., joie ‘joy’). The morphologically complex word exploiter ‘to exploit’, with a pronounced t, can be used to indicate that the stem exploit is spelled with a silent t. We asked whether 8-year-old children benefited from such cues to learn new spellings. Children read silently stories which included two target nonwords, one presented in an opaque condition and the other in a morphological condition. In the opaque condition, the sentence provided semantic information (e.g., a vensois is a musical instrument) but no morphological information that could justify the spelling of the target word’s final sound. Such justification was available in the morphological condition (e.g., the vensoisist plays the vensois instrument, which justifies that vensois includes a final silent s). Thirty minutes after having read the stories, children’s orthographic learning was assessed by asking them to choose the correct spelling of each nonword from among three phonologically plausible alternatives (e.g., vensois, vensoit, vensoie). Children chose correct spellings more often in the morphological condition than the opaque condition, even though the root (vensois) had been presented equally often in both conditions. That is, children benefited from information about the spelling of the morphologically complex word to learn the spelling of the stem.